Determinants of Dysfunctional Audit Behaviour: The Moderating Role of Ethical Values - Mensah, N. (University of Ghana, 2023)
This research examines the factors that influence auditors to engage in dysfunctional audit behaviour. It investigates this phenomenon from a different theoretical lens by adapting the Stimulus, Capability, Opportunity, Rationalization, Ego (S.C.O.R.E) Model to underpin the research. It is an attempt to examine this phenomenon from a developing country perspective as cases where auditors are found culpable in corporate scandals and failures in the last decade have been on the rise. It examines the constructs in the S.C.O.R.E Model as possible factors that influence auditors to engage in dysfunctional audit behaviour. Furthermore, the study introduces ethical values as moderating variable in the relationship between the factors identified and dysfunctional audit behaviour. The research is quantitative and employs the philosophical assumptions of the positivism paradigm to underpin the research. A total of 411 responses were received from the questionnaires administered to the individual auditors. The predicted relationships were examined using the Partial Least Square Structural Equation Modelling technique (PLS-SEM) and SmartPLS software was used to analyze the data. Time budget pressure, capability and rationalization are found to have a significant positive relationship with dysfunctional audit behaviour. The findings imply that auditors engage in dysfunctional audit behaviour when they are faced with intense pressure to complete audit procedures within a limited period. Moreover, auditors who possess special skills and are influential during audits are likely to engage in dysfunctional audit behaviour with the mindset that they can get away with such behaviours or that they will go unnoticed. The results indicate that ethical value is significantly and negatively related to dysfunctional audit behaviour. This suggests that auditors are unlikely to engage in dysfunctional audit behaviour when they possess strong ethical values. The result further reveals that ethical values moderate favourably the relationships between time budget pressure and dysfunctional audit behaviour as well as ego and dysfunctional audit behaviour.
MPhil. Accounting
Keywords: auditors; dysfunctional; behaviour